Вплив “великого терору” 1937-1938 рр. на економічні процеси в УРСР - Васильєв, В. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2004)
The author based on the analysis of new archival documents investigated how the negetave aspects of economic processes of 1930th impacted the mentality of Communist party’s leaders, who, in their turn, initiated new waves of political repression. Besides the role and results of state terror in the administration of some branches of industry in the Soviet Ukraine in the 1937–1938 were found out.